2019
DOI: 10.1371/journal.pone.0223210
|View full text |Cite
|
Sign up to set email alerts
|

Major drug resistance mutations to HIV-1 protease inhibitors (PI) among patients exposed to PI class failing antiretroviral therapy in São Paulo State, Brazil

Abstract: BackgroundProtease inhibitors (PI) are especially important in salvage therapy. Previous treatment failure with a PI containing regimen may elicit resistance mutations, reducing PI susceptibility and limiting treatment options. The aim of this study was to describe major PI mutations among patients exposed to at least one PI to evaluate predictors of mutation emergence and the impact of subtypes on resistance.MethodologyPartial HIV-1 pol sequences (Sanger Sequencing) from patients exposed to PI with virologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…As previously reported by Soldi et al in a subtype F highly-prevailing setting, the presence of NRTI mutations was associated to some PI/r resistance mutations (i.e. I50LV) in patients failing PI/r treatment 24 . Indeed, some studies revealed that some inserts at the P6 region within the Gag gene may favor virus escape from nucleoside reverse transcriptase inhibitors (NRTI) through greater accumulation of resistance mutations, leading to high level of resistance to this drugs class 25 .…”
Section: Discussionsupporting
confidence: 74%
“…As previously reported by Soldi et al in a subtype F highly-prevailing setting, the presence of NRTI mutations was associated to some PI/r resistance mutations (i.e. I50LV) in patients failing PI/r treatment 24 . Indeed, some studies revealed that some inserts at the P6 region within the Gag gene may favor virus escape from nucleoside reverse transcriptase inhibitors (NRTI) through greater accumulation of resistance mutations, leading to high level of resistance to this drugs class 25 .…”
Section: Discussionsupporting
confidence: 74%
“…Nine PR drugs have been approved for clinical AIDS treatment, including SQV, indinavir (IDV), ritonavir (RTV), NFV, amprenavir (APV), LPV, ATV, tipranavir (TPV), and darunavir (DRV). While some studies suggest that resistance to PIs is not as common as resistance to other antiretroviral drugs, others have found that resistance can emerge within weeks to months of starting treatment, with PI resistance becoming increasingly prevalent in HIV-positive patients (16,17). For instance, a recent study by Obsa et al identified that out of 56 patients analyzed, 14 (25%) had PI resistance mutations, significantly higher than figures recorded for nonnucleoside RT inhibitors (NNRTIs) (5/56, 9%) and IN inhibitors (2/56, 4%) (18).…”
Section: Discussionmentioning
confidence: 99%
“…This could mean that some Gag mutations with high frequencies in patients failing PI/r may have been induced during RTI treatment, showing its role in resistance to PI/r, as Romero Soldi et al in 2019 showed that NRTI mutations and subtype F were associated to the emergence of some PI/r drug resistance mutations like I50LV in patients failing PI/r treatment 21 . Indeed, some studies revealed that some inserts at the P6 region within the Gag gene may favor virus escape from nucleoside reverse transcriptase inhibitors (NRTI) through greater accumulation of resistance mutations, leading to high level of resistance to this drugs class 22 .…”
Section: Discussionmentioning
confidence: 99%